Outcomes After Surgical Treatment of Adolescent Intra-articular Distal Humerus Fractures. Issue 8 (December 2016) - Cook, Jay B.; Riccio, Anthony I.; Anderson, Terrence; Chen, Weichen; Shaha, Steven H.; Wimberly, Robert L.
Abstract : Background: To determine the radiographic and clinical outcomes of the surgical management of adolescent intra-articular distal humerus fractures. Methods: We performed a retrospective review of the clinical and radiographic outcomes of 31 consecutive adolescent patients surgically treated for acute distal humerus intra-articular fractures. Nine patients returned for objective measures of range of motion, strength testing, and completion of validated outcome scores including the Mayo Elbow Performance Score (MEPS); The Disabilities of the Arm, Shoulder, and Hand Score (DASH); and the SF-36. Results: The average age at the time of injury was 13.5 years (range, 12 to 16 y) with a mean follow-up of 1.22 years (range, 9 d to 5.5 y). Multiple surgical approaches were performed. Overall, the active range of motion for our patients was 10.7 to 133.9 degrees with a mean arc of 123.4 degrees. AO classification type C2 and C3 injuries lost significantly more motion than other fracture patterns. Twelve patients sustained perioperative nerve palsies that resolved by final follow-up; seven of these nerve injuries were iatrogenic and sustained during a Bryan-Morrey tricepital slide approach. Eight patients required implant removal; 7 of these patients had prominent olecranon screws after an olecranon osteotomy. Including postoperative neuropathies, there were 20 complications in 15 patients. Thirteen complications in 9 patients required a return to the operating room. Of the 9 patients who returned for objective testing, there was no statistically significant loss of range of motion or strength of the injured extremity when compared with the uninjured limb. The MEPS revealed 6 excellent, 1 good, and 2 fair results. The average DASH score was 5.1 (range, 0 to 19.1) and the physical (average 55.7; range, 47.4 to 59.0) and mental components (average 54.2; range, 29.8 to 63.4) of the SF-36 were comparable. Conclusions: After surgical intervention for an adolescent intra-articular distal humerus fracture, one can expect no significant loss of motion or strength. The reported outcomes are not all excellent. The peri-operative complication rates are high and may be related to surgical approach and fracture pattern. Level of Evidence: Level IV.